2019
DOI: 10.1128/aem.00402-19
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Strain DSM 29784 Modulates the Cecal Microbiome, Concentration of Short-Chain Fatty Acids, and Apparent Retention of Dietary Components in Shaver White Chickens during Grower, Developer, and Laying Phases

Abstract: This study investigated the efficacy of a single strain of Bacillus subtilis (SSB) in modulating the composition of cecal microbiota and its link to the concentration of short-chain fatty acids (SCFA) and apparent retention (AR) of components. A total of 720, 4-week-old Shaver White chicks were allotted to control (CON), 1.1Eϩ08 (low, LSSB), 2.2Eϩ08 (medium, MSSB), or 1.1Eϩ09 (high, HSSB) CFU/kg of diet groups. At grower (10-week), developer (16-week), and laying (28-week) phases, excreta and cecal digesta sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 102 publications
9
23
0
Order By: Relevance
“…Thus, feed supplementation by the cranberry products in broilers could improve production efficiency similar to BACI. Conversely, Bacteroidetes help to promote intestinal digestion, nutrient utilization, and hind gut fermentation of substrates to produce SCFA, as well as promoting the conversion of the absorbed SCFA to more complex compounds in the liver ( 63 ). We found that blueberry by-products significantly increased the abundances of Bacteroidetes more than any other treatments, particularly in the ceca samples, presumably related to the increase of BW during the growing period and to the reduction of blood serum enzymes like ALT and LIP.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, feed supplementation by the cranberry products in broilers could improve production efficiency similar to BACI. Conversely, Bacteroidetes help to promote intestinal digestion, nutrient utilization, and hind gut fermentation of substrates to produce SCFA, as well as promoting the conversion of the absorbed SCFA to more complex compounds in the liver ( 63 ). We found that blueberry by-products significantly increased the abundances of Bacteroidetes more than any other treatments, particularly in the ceca samples, presumably related to the increase of BW during the growing period and to the reduction of blood serum enzymes like ALT and LIP.…”
Section: Discussionmentioning
confidence: 99%
“…Many yeast species are recognized safe by many regulatory authorities such as Qualified Presumption of Safety status assigned by the European Food Safety Authority, the Association of American Feed Control Officials and Canadian Food Inspection Agency. However, in general, most commercial probiotic feed additives for poultry are of bacterial preparations e.g., (49)(50)(51)(52)(53). The few non-bacterial (yeast or fungal) probiotics includes Aspergillus oryzae (54,55), Candida pintolopesii (54), Candida saitoana, Saccharomyces bourlardii (56), and S. cerevisiae (57).…”
Section: Live Whole Yeastmentioning
confidence: 99%
“…Similarly, antibiotics can change the microbial composition in the mouse gut and then decrease the production of SCFAs, ultimately impaired reparation of MI [43]. Moreover, several other studies also demonstrated that reprogramming of gut microbiota or transplantation of fecal microbiota could modulate the SCFAs to prevent obesity and cerebral ischemic stroke [44][45][46]. In addition to the gut microbiota, dietary composition also influences the production of SCFAs and subsequent functional readout.…”
mentioning
confidence: 99%